Sesbania bispinosa, a new host of a begomovirus-betasatellite complex in Pakistan. Issue 1 (2nd January 2016) - Zaidi, Syed Shan-E-Ali; Amin, Imran; Iqbal, Zafar; Pervaiz akhtar, Khalid; Scheffler, Brian E.; Mansoor, Shahid
Abstract: Symptoms of severe leaf curling, yellowing and vein thickening, typical of begomovirus infection, were observed on Sesbania bispinosa grown in cotton leaf curl disease affected cotton fields in Pakistan. A begomovirus and its associated betasatellite were amplified and sequenced from these affected plants. Complete nucleotide sequence showed that a monopartite begomovirus named Pedilanthus leaf curl virus (PeLCV) is associated with the disease and it shared highest sequence identity (98.73%) with a clone previously reported from soybean. Characterization of the betasatellite showed that it had highest sequence identity (96–97%) with Tobacco leaf curl betasatellite (TbLCB), previously isolated from soybean. Our data shows the expansion of the host range of begomovirus-betasatellite complexes. To the best of our knowledge, this is the first occurrence of PeLCV and TbLCB on S. bispinosa .